How Counseling Based on Acceptance and Commitment Therapy and Supported With Motivational Interviewing Affects the Perceptions of Treatment Motivation in Patients Diagnosed With Schizophrenia: A Qualitative Study. (September 2021) - Yıldız, Erman; Aylaz, Rukuye
Background: Lack of motivation is a common phenomenon in treatment of schizophrenia. Despite information that various psychosocial approaches may help overcome lack of motivation, their content and nature remain uncertain. However, in recent years, there is an increasing interest in psychosocial interventions such as acceptance and commitment therapy (ACT) and motivational interviewing (MI) techniques in approaching individuals diagnosed with schizophrenia (IDSs). In this study, the therapeutic models of ACT and MI were combined to create an innovative integrative approach to address the problem of lack of motivation in IDSs. Aims: This study was conducted to determine how a counseling program based on ACT and supported with MI affected the perceptions of treatment motivation in IDSs. Method: This study addressed the qualitative aspects of a doctoral dissertation designed as a quasi-experimental study that gathered both quantitative and qualitative data. Results: As a result of the content analysis, three main themes and 10 categories that motivated IDSs for compliance with regular treatment were developed. The participants in the experimental group expressed a focused treatment motivation to participate in daily life activities and social relations, acceptance of illness, satisfaction with life despite side effects and leading a value-oriented life in comparison with the control group. Conclusions: Counseling based on ACT and supported with the MI technique is effective in improving treatment motivation in IDSs. This counseling may be implemented as an effective psychiatric nursing intervention for IDSs.